Sekentei and objectively-measured physical activity among older Japanese people: a cross-sectional analysis from the NEIGE study - Hiroshi Murayama; Shiho Amagasa; Shigeru Inoue; Takeo Fujiwara; Yugo Shobugawa (BMC, 2019)
Abstract Background The concept of sekentei (social appearance), defined as sensitivity about one's reputation, reflects Japanese behavioral principles and involves pressure to conform to social norms, particularly among people living in rural areas. However, data regarding the relationship between sekentei and health behaviors are sparse. In this study, we examined the relationship between sekentei and objectively-measured physical activity among community-dwelling older people in Japan. Methods We used data from the Neuron to Environmental Impact across Generations Study (NEIGE Study), which is a prospective cohort study of randomly-sampled community-dwelling individuals aged 65-84 years living in Tokamachi City, Niigata Prefecture, Japan. The baseline survey was conducted in 2017 and included 527 independent older people. We analyzed the baseline data cross-sectionally. To measure activity behaviors, participants wore a tri-axial accelerometer for seven consecutive days. Physically active individuals were defined based on the World Health Organization recommendation guidelines on physical activity. Sekentei was measured using the 12-item Sekentei Scale (score range: 12-60). Results After excluding 15 people for whom we had three or fewer days of valid accelerometer-assessed activity data, we used data from 512 participants in our analysis (average 73.4 years old; 46.9% men). Physically active individuals made up 22.3% of the sample, and the proportion of physically active men was higher than that of women. A logistic regression analysis showed that higher levels of sekentei were inversely associated with physical activity after adjusting for demographic factors, socioeconomic status, and health conditions (odds ratio [95% confidence interval]: 0.58 [0.36-0.91] for every 10-point increase in the Sekentei Scale score). This association was stronger in women than in men (0.66 [0.34-1.26] for men and 0.51 [0.26-1.00] for women). Conclusions Our findings indicate that an individual's sense of sekentei may be an important socio-cultural factor affecting their level of physical activity. Culturally appropriate approaches may be beneficial in addressing insufficient physical activity in older adults.